2021
DOI: 10.14739/2310-1210.2021.5.237403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term training on heart rate variability, central hemodynamics and physical working capacity in female swimmers with different sports qualifications

Abstract: The aim of this study was to compare the indices of heart rate variability, central hemodynamics and physical working capacity in female swimmers with different sports qualifications. Materials and methods. The indices of heart rate variability (HRV), central hemodynamics (CH) and physical development (PD) were studied in 44 female swimmers (mean age 15.00 ± 0.36 years, swimming experience – 7.40 ± 0.35 years) depending on their sports qualifications (MSIC, MS, CMS, first- and second-class athletes). To analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…A comparison of results obtained in high-class female swimmers, examined in 2006 (Mykhaliuk, 2006) and 2021 (Mykhaliuk et al, 2020;Mykhaliuk et al, 2021aMykhaliuk et al, , 2021b indicates that present-day swimmers were on average 0.5 years (p=0.345) younger, started swimming training 1.2 years (p=0.08) earlier, had no differences in body length, and had insignificantly greater body weight (p=0.152). For HRV parameters, Mo was significantly less by 14.22% (p=0.044), ARI � greater by 51.1% (p=0.029), SI by 78.6% (p=0.048) and the upward trend in AMo/D by 55.38% (p=0.108) was revealed.…”
Section: Results Of the Studymentioning
confidence: 96%
See 3 more Smart Citations
“…A comparison of results obtained in high-class female swimmers, examined in 2006 (Mykhaliuk, 2006) and 2021 (Mykhaliuk et al, 2020;Mykhaliuk et al, 2021aMykhaliuk et al, , 2021b indicates that present-day swimmers were on average 0.5 years (p=0.345) younger, started swimming training 1.2 years (p=0.08) earlier, had no differences in body length, and had insignificantly greater body weight (p=0.152). For HRV parameters, Mo was significantly less by 14.22% (p=0.044), ARI � greater by 51.1% (p=0.029), SI by 78.6% (p=0.048) and the upward trend in AMo/D by 55.38% (p=0.108) was revealed.…”
Section: Results Of the Studymentioning
confidence: 96%
“…When comparing the studied indicators of elite female swimmers in 2006 (Mykhaliuk, 2006) and 2021 (Mykhaliuk et al, 2020;Mykhaliuk et al, 2021aMykhaliuk et al, , 2021b, it was revealed that in 18 female swimmers with these sports qualifications examined in 2006 (average age 21.0±1.4 years, swimming experience 11.3±1.4 years, body length � 175.0±0.9 cm, body weight � 61.5±0.9 kg) Mo…”
Section: Results Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of obtained results of the action is the third principal feature in the process of developing the motor skill. The motor skill, if it is well developed and improved in the practice of training, practically does not disappear, even during long breaks caused by sports injuries, long illnesses, other factors (Tishchenko, Sokolova, & Popov, 2019;Shchepotina et al, 2021;Mykhaliuk, Syvolap, & Horokhovskyi, 2021).…”
Section: Discussionmentioning
confidence: 99%